Mini-Mental State Examination norms in a community-dwelling sample of elderly with low schooling in Brazil Normas do Mini-Exame do Estado Mental para uma amostra de idosos com baixa escolaridade residentes na comunidade no Brasil - Jerson Laks; Elienai Maria Rubim Baptista; Ana Lúcia Barros Contino; Estevão Oliveira de Paula; Eliasz Engelhardt (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2007)
The objective of this study was to assess Mini-Mental State Examination norms of a functionally normal sample of community-dwelling elderly. Illiterate and low-educated subjects who scored less than 5 on the Pfeffer Functional Activities Questionnaire (PFAQ) [n = 397; female = 269; mean age = 72.15 (SD = 7.24) years] had the 5th, 25th, 50th, and 75th percentiles calculated according to age (65-74; 75-84 years). Overall MMSE score was 21.97 (SD = 4.48). Mean MMSE for illiterate younger individuals was 19.46 (SD = 3.47), and the quartile distribution was 14, 17, 19, and 21. MMSE of subjects with 1-8 years of schooling was 23.90 (3.87), and the distribution was 15, 22, 24, and 27. MMSE of older illiterate subjects was 18.11 (SD = 3.63), and the distribution of scores was 13, 16, 18, and 20, whereas subjects with 1-8 years of schooling scored 23.81 (SD = 4.01) and the distribution was 15, 22, 24, and 27. These MMSE normative data may help improve the detection of cognitive impairment in Brazil, mainly in the primary clinical setting. Avaliar normas do Mini-Exame do Estado Mental (MEEM) de acordo com a idade e escolaridade de idosos vivendo na comunidade. Calcularam-se os quartis do MEEM para idosos com 65 a 74 e 75 a 84 anos, analfabetos e com 1-8 anos de escolaridade, com pontuação menor que cinco no Questionário de Atividades Funcional de Pfeffer (QAF) [n = 397; feminino = 269; idade = 72,15 (dp = 7,24) anos].O MEEM total foi 21,97 (dp = 4,48). Nos indivíduos mais jovens, o MEEM entre analfabetos foi 19 (3,47) com quartis de 14, 17, 19, 21. O MEEM dos com 1-8 anos de escolaridade foi 23,90 (dp = 3,87), e a distribuição foi 15, 22, 24, 27. O MEEM dos analfabetos mais idosos foi 18,11 (dp = 3,63) com quartis de 13, 16, 18, 20, enquanto a pontuação dos sujeitos com 1-8 anos foi 23,81 (dp = 4,01), quartis de 15, 22, 24, 27. Os dados de normatização do MEEM podem ajudar o reconhecimento de distúrbios cognitivos no Brasil, principalmente no atendimento primário.